Pengaruh Produk Minuman Asam Jawa (Tamarindus indica) terhadap Kekerasan Permukaan Resin Komposit - Zain, Haura Hafizhah; Harniati, Etny Dyah (Jurnal Material Kedokteran Gigi; Vol 9 No 2 (2020): JMKG Vol 9 No 2 September 2020DO - 10.32793/jmkg.v9i2.414, 2021)
Resin composite is commonly used in dental material filling which has primacy physical and mechanical properties. Nonohybrid composite is the latest advancement in resin composite has been the use of nanotechnology in development fillers. The properties that have an essensial role is surface hardness of resin composite which directly contact with saliva, food and drink. The aim of this research was to determine the effect of tamarind beverages (Tamarindus indica) on surface hardness of nanohybrid resin composite. The methods used in this research is post test with control group design. Samples were made using the mold with diameter 15mm and thickness 2mm (n=32). Filtek Z250xt shades A3 was used in this research. Samples were divided into four groups, aquadest (group I), tamarind beverage 2% (group II), 6% (group III), and 15% (group IV), then immersed for 14 minutes in an incubator with temperature 37°C. Samples were measured using Vickers Hardness Tester. The data were analyzed using One Way ANOVA. The results of surface hardness’s means, group I (87,65±7,47 VHN), group II (84,73±3,81 VHN), group III (83,95±4,79 VHN), and group IV (81,85±4,04 VHN). The results of data analysis showed that data is distributed normally and homogen (p>0,05), even though parametric test showed significant’s value is p=0,194 (p<0,05). Immersed tamarind beverages is not significantly reduced the surface hardness of nanohybrid resin composite.